Effect of supervised high-intensity interval training on haemostasis in patients with coronary artery disease: a randomised controlled trial. (3rd October 2022) - Kristiansen, J; Grove, E L; Sjurdarson, T; Rasmussen, J; Mohr, M; Kristensen, S D; Hvas, A M
Abstract: Background: Regular exercise training is recommended for patients with stable coronary artery disease (CAD), because it improves quality of life and reduces cardiovascular mortality and hospital admissions. CAD patients benefit from anti-thrombotic therapy and may have a pro-coagulant condition compared to healthy individuals. Long-term exercise training may reduce platelet aggregation and coagulation and increase fibrinolysis. Purpose: We aimed to investigate if supervised high-intensity interval training affects haemostasis in patients with stable CAD. Methods: We randomised stable CAD patients to supervised high-intensity interval training or standard care. High-intensity exercise training was performed on rowing ergometers three times weekly for 12 weeks. Blood samples were obtained in all patients prior to randomisation (baseline) and after 6 and 12 weeks. We evaluated platelet aggregation with the Multiplate® Analyzer, thrombin generation using the Calibrated Automated Thrombogram and fibrinolysis employing an in-house clot lysis assay. Between group differences were evaluated with mixed model analysis using SPSS. According to our sample size calculation, we have a statistical power of 88% to detect a difference of 25% in clot lysis time. Results: A total of 142 patients with stable CAD (mean age 67±9 years, 83% males) completed the study; 64 in the exercise group and 78 in the control group. The weekly average active training duration was 54 min, and adherence to training was 97%. When comparing the two groups (exercise vs. standard care) from baseline to post intervention, we found no significant changes in ADP-induced platelet aggregation (difference between baseline and 12 weeks (Δ) 11 AU·min, 95% confidence interval (CI): −46–68 in the exercise group and Δ24 AU·min, 95% CI: −28–77 in the standard care group, p=0.52), thrombin generation (endogenous thrombin potential Δ45 nM·min, 95% CI: −77–166 in the exercise group and Δ103 nM·min, 95% CI: −7–212 in the standard care group, p=0.18) or fibrinolysis (50% clot lysis time Δ62 sec, 95% CI: −136–261 in the exercise group and Δ215 sec, 95% CI: 38–391 in the standard care group, p=0.39). Conclusion: High-intensity interval training did not have major effects on platelet aggregation, thrombin generation nor fibrinolysis in patients with stable CAD. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Aarhus UniversityThe Faroese Health Research Foundation (Sjúkrakassagrunnurin)